PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THREE STAY ONE STRAY (TSOS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 023 PULAU KIJANG KECAMATAN RETEH - Rosdianah Rosdianah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The purpose of this study was to improve student learning outcomes by applying the Type Three Stay One Stray (TSOS) Cooperative Learning Model. This research was conducted at 023 Public Primary School Pulau Kijang, Reteh District. This research is a classroom action research which consists of two cycles. Each cycle consists of action planning, action, observation and reflection. The results of the study show, seen from the initial data, students who completed as many as 6 people with a class average of 65. In the first cycle, there was an increase of an average of 71.3 and in the second cycle there was an increase with a class average of 86.4. Then there is an overall increase from the basic score to the second cycle of 21.4. while the number of students who completed in the first cycle were 9 people with a percentage of 64.2%, in the second cycle as many as 12 people with a percentage of 85.7%. the increase in the percentage of completeness from the basic score to the second cycle was 42.9%.